Fibres, Globules, Cells: William Blake and the Biological Individual - Lee, Tara (Romanticism on the Net)

(untitled) (Université de Montréal, 2021)
Scientific discoveries have often been preceded by shifts in ways of seeing. This article argues that William Blake’s critique of eighteenth-century medicine is grounded upon a Romantic view of organic form shared by contemporary scientists such as Lorenz Oken. Eighteenth-century anatomists and microscopists sought to isolate the elementary unit of living matter, which was thought to be the fibre by some, and the globule by others. At the beginning of the nineteenth century, however, scientists began to question the assumption that a living organism was an agglomeration of parts, framing the individual part as something produced only by the division and analysis of the whole. In doing so, they set the terms for the development of modern cell theory in the 1830s. Blake’s evocative descriptions of the fibres and globules which make up living organisms show him undermining the reductionist search for a fundamental unit of life. However, an artist rather than a biologist, Blake is also able to use a metaphorical language of graphical form to challenge his readers to see individuality as a matter of perspective rather than a matter of fact, ultimately helping to craft the epistemic environment that would make later theories of the organism possible.